Quem é essa profissional?: trabalho docente no ensino superior privado e relações sociais de sexo - Jacqueline da Silva Figueiredo Pereira (2015)
From the last decades of the twentieth century there have been significant changes in economic structures, social and policy worldwide, including the intensification of globalization, the hegemony of neoliberalism and the advancement of technologies that are impacting the States / Governments. Important changes have also been observed in the modes of objectification of labor relations. These changes in the workplace have led to changes in the way / the workers / as they relate to the work context. The changes in the world of work and its impact on the subjectivities of / the workers / the reach numerous categories of workers, and that teaching is constituted as another living space of these transformations. The resurgence of teaching as the focus of interest of researchers and organizations representing teachers signal for a precarious teaching and identify an identity crisis experienced by these / professional, that has influenced the construction of the professional identity of / the teachers / the. This research glanced at the private higher education in order to identify and analyze the knowledge produced, deployed and used in everyday practice of teaching by teachers who work in the private higher education and the construction of the professional identity of teachers, which the analysis category the social relations of gender. The survey was conducted in an institution of higher education, located in a municipality that is part of the Greater Belo Horizonte, 10 years ago. We conducted semi-structured interviews and questionnaires to teachers / the IES investigated. The IES study belongs to a mining business group, which has several IES and educational institutions that offer Basic and Vocational Education, founded in the 60s, during the first expansion of higher education via opening, this level of education, the initiative private. This school system is present in more than 100 cities in Minas Gerais. The survey revealed that in the private higher education is still marked by gender inequalities, precarious teaching in private higher education, illness and suffering at work by both teachers female and male, but the experience of pleasure at work is more common among female teachers than among male teachers.